Efficacy of Balanced Nutrition Comic as a Learning Medium in Nutrition Education Intervention for Primary School-Age Children in Sampang District - Moh. Ari Wibowo; Heni Adhianata (Journal of Ners and Midwifery, 2023)
Indonesian skipping breakfast is common among school-age children. Several studies have revealed the importance of breakfast and its positive effects on health and productivity, especially for school-aged children. Schools are the most efficient place for health education targeting dietary or other health-related changes in school-age children. Balanced nutrition education can teach and demonstrate the importance of breakfast, healthy consumption and a balanced diet for the health of school-age children. The purpose of this study was to provide a balanced nutrition education intervention for elementary school-aged children in Sampang regency as an effort to improve the quality of nutrition knowledge and practices of children. Nutrition education interventions are carried out using comic compiled based on balanced nutrition guidelines in Indonesia. A quasy-experiment using pretest-posttest and control group and descriptive design were used in this research. A structured questionnaire which comprised of personal/demographic information, nutrition knowledge, attitude towards nutrition and nutritional practices was conducted to 75 students. The average score of nutrition knowledge from both the control and intervention group was still below 50%. Nutrition education intervention using nutrition balanced comic was significantly increase nutrition kowledge and nutritonal practices of students, 75.73 ± 10.33 and 52.31 ± 10.61 respectively.  Nutrition education through balanced nutrition comics provides new knowledge in a more interesting way for students. Fun learning conditions will make student more attentive and able to capture applicative value from the messages conveyed, so that students’ nutrition practices are also higher compared to before the intervention